A study on the oral health status and care of quadriplegic patients at the Philippine orthopedic center, Quezon City from September 1990 to December 1990 - Castaneda, Milagros Nazarene C.
Due to the paralysis of their upper and lower extremities, quadriplegic patients have difficulty in maintaining proper dental hygiene and care. Hence, to be able to know the oral health status of quadriplegic patients as well as methods to improve and or maintain their oral health status, this study was conducted. 18 quadriplegic patients at the Philippine Orthopedic Center were interviewed regarding their medical and dental history and oral hygiene practices. Then an oral examination was done to determine their dental status and treatment needs. The study showed that the mean DMF teeth is 17.11 while the mean number of sextants with gingival bleeding is 1.1 ; sextants with calculus is 4.0 ; 0.3 sextant has shallow pocket while 0.6 sextant were not applicable for coding. The most prevalent CPITN score was for calculus which is 83% for the whole population. 11% was recorded for shallow pocket while 6% was recorded for gingival bleeding. 94% of the population need restorative treatment, 33% need surgical extractions, 100% need periodontal treatment and 28% need prosthodontic rehabilitation. 100% of the subjects brush their teeth. 17% brush their own teeth thrice a day using an adapted type of toothbrush while 83% have their teeth brushed by their caretakers using an ordinary type of toothbrush with varying frequency.